גילוי פנים: יחסי שירה, צילום וזיכרון במחזור השירים "ערב יהודי קראסניסטאוו" - ברם, שחר (מכאן, 2016)
Avot Yeshurun’s sequence of poems, Erev Yehudei Krasnistav, in HaShever HaSuri Africani (1974) depicts the poet contemplating whether to participate in the annual memorial service in honor of his hometown in which, as part of the ceremony, photographs of the dead - relatives and friends - will be shown. Do photographs, which resurrect the past, burden one with more guilt due to such collective circumstances? The sequence of poems reveals more than the poet’s feeling of guilt enhanced by rituals and ceremonies; it enables the reader to examine the concealed rivalry between different means of representation, such as photographs, dreams and poetry. This essay explores the rivalry between various ways in which memories are formed, a rivalry that torments the poet in his attempt to take control of his past. The essay represents an aspect of Yeshurun’s poetry that has received very little attention: the influence of photography on his poetics.